Canned heat [nuclear waste storage]. - Zorpette, G.
Fifty-nine years after the dawning of the nuclear age, not one country has managed to find anything more than a temporary resting place for its tons of nuclear detritus. Improvements in the design and operation of power reactors and scattered shortages of electricity this past summer have made the waste problem the biggest obstacle to any resurgence of nuclear power. Such a reemergence is needed, supporters say, to reduce acid rain and to keep more than a billion tons of greenhouse gases from fossil fuel plants out of the atmosphere over the next 10-20 years. It would also help reduce the dependence of the US, European, and Japanese economies on oil, thereby lessening their exposure to the seemingly endless cycles of instability, violence, and terrorism in parts of the Middle East. But there is no agreement anywhere as yet on a permanent solution for dealing with the waste, which will remain radioactive enough to harm human beings for thousands of years. Still, consensus over a temporary fix has finally emerged in the United States, Europe, and Japan. With dry-cask storage, as the technique is known, workers seal spent nuclear fuel or high-level waste in metal or metal-and-concrete containers that are guarded and monitored, typically in a fenced-in compound or warehouse near the reactor where the fuel was used. The casks are roughly 5 meters tall, 2.5 meters in diameter, and weigh more than 100 metric tons when loaded. After decades of uncertainty, utilities finally have a direction, at least, and a sorely needed one
Keywords: Dry-cask storage; Fenced-in compound; High-level nuclear waste; Metal containers; Metal-and-concrete containers; Nuclear waste storage; Power reactors; Spent nuclear fuel; Warehouse